Pengaruh Kualitas Kompetensi Sumber Daya Manusia, Penggunaan Teknologi Informasi Dan Pengalaman Kerja Terhadap Kualitas Laporan Keuangan Bumdes Se-Kecamatan Sukawati - I Wayan Yadi Linggia Swandika; Kadek Dewi Padnyawati; Ni Putu Trisna Windika Pratiwi (UNHI Press, 2023)
This thesis is a research that describes the influence of human resource competence, use of information technology, and work experience on the quality of financial reports of Villageowned enterprises in Sukawati sub-district. The reason behind the researcher's interest in making this thesis, is based on observations and initial interviews conducted by researchers with Village-owned enterprises in Sukawati sub-district, where the financial reports produced by Village-owned enterprises are not in accordance with applicable standards. Researchers found indications why the quality of financial reports produced by Village-owned enterprises was not up to standard, namely because of the lack of accounting competence possessed by employees, not yet maximal use of information technology, and the lack of work experience of Village-owned enterprises management in the accounting field. The population in this study are users of financial statements Village-owned enterprises administrators in Sukawati District, totaling 36 people, the sampling technique used was saturated sampling technique. The number of samples used in this study were 36 respondents. The data analysis technique in this study used multiple linear regression analysis which was processed with the SPSS statistic 25 program. The results showed that (1) the competence of human resources has a positive and significant effect on the quality of financial reports, (2) the use of information technology has no effect on the quality of financial reports, (3) work experience has a positive and significant effect on the quality of financial reports